Cytidine deamination induced HIV-1 drug resistance - Mulder, Lubbertus C. F. (National Academy of Sciences, 2008)
The HIV-1 Vif protein is essential for overcoming the antiviral activity of DNA-editing apolipoprotein B mRNA editing enzyme, catalytic polypeptide 3 (APOBEC3) cytidine deaminases. We show that naturally occurring HIV-1 Vif point mutants with suboptimal anti-APOBEC3G activity induce the appearance of proviruses with lamivudine (3TC) drug resistance-associated mutations before any drug exposure. These mutations, ensuing from cytidine deamination events, were detected in >40% of proviruses with partially defective Vif mutants. Transfer of drug resistance from hypermutated proviruses via recombination allowed for 3TC escape under culture conditions prohibitive for any WT viral growth. These results demonstrate that defective hypermutated genomes can shape the phenotype of the circulating viral population. Partially active Vif alleles resulting in incomplete neutralization of cytoplasmic APOBEC3 molecules are directly responsible for the generation of a highly diverse, yet G-to-A biased, proviral reservoir, which can be exploited by HIV-1 to generate viable and drug-resistant progenies.